Posttranslational Modification of Human Glyoxalase 1 Indicates Redox-Dependent Regulation - Birkenmeier, Gerd; Stegemann, Christin; Hoffmann, Ralf; Günther, Robert; Huse, Klaus; Birkemeyer, Claudia (PLOS ONE, 2010)
Background Glyoxalase 1 (Glo1) and glyoxalase 2 (Glo2) are ubiquitously expressed cytosolic enzymes that catalyze the conversion of toxic α-oxo-aldehydes into the corresponding α-hydroxy acids using L-glutathione (GSH) as a cofactor. Human Glo1 exists in various isoforms; however, the nature of its modifications and their distinct functional assignment is mostly unknown. Methodology/Principal Findings We characterized native Glo1 purified from human erythrocytes by mass spectrometry. The enzyme was found to undergo four so far unidentified posttranslational modifications: (i) removal of the N-terminal methionine 1, (ii) N-terminal acetylation at alanine 2, (iii) a vicinal disulfide bridge between cysteine residues 19 and 20, and (iv) a mixed disulfide with glutathione on cysteine 139. Glutathionylation of Glo1 was confirmed by immunological methods. Both, N-acetylation and the oxidation state of Cys19/20, did not impact enzyme activity. In contrast, glutathionylation strongly inhibited Glo1 activity in vitro. The discussed mechanism for enzyme inhibition by glutathionylation was validated by molecular dynamics simulation. Conclusion/Significance It is shown for the first time that Glo1 activity directly can be regulated by an oxidative posttranslational modification that was found in the native enzyme, i.e., glutathionylation. Inhibition of Glo1 by chemical reaction with its co-factor and the role of its intramolecular disulfides are expected to be important factors within the context of redox-dependent regulation of glucose metabolism in cells.